2007
DOI: 10.1056/nejmc071583
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Oropharyngeal Cancer

Abstract: Joura EA, Leodolter S, Hernandez-Avila M, et al. Efficacy of a quadrivalent prophylactic human papillomavirus (types 6, 11, 16, and 18) L1 virus-like-particle vaccine against high-grade vulval and vaginal lesions: a combined analysis of three randomised clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, specialized centers or tertiary hospitals with selective referral may not be that representative for both OPSCC cases and healthy controls, as intended. Indeed, Maura Gillison [ 20 ], in response to a letter questioning the representativeness of their findings [ 1 ], stated that the authors “cannot exclude the possibility that subjects who did not have traditional risk factors were more likely to participate in [their] study as it was performed in a hospital and was not population-based”. Unfortunately, the scientific community mostly neglected this information, thus limiting the transferability of the findings to the general population and the interpretation of the correlation between HR-SB and OPSCC in their study [ 1 ]; instead, they interpreted the data from their study as evidence for a causative involvement of HR-SB in the etiology of OPSCC in general.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specialized centers or tertiary hospitals with selective referral may not be that representative for both OPSCC cases and healthy controls, as intended. Indeed, Maura Gillison [ 20 ], in response to a letter questioning the representativeness of their findings [ 1 ], stated that the authors “cannot exclude the possibility that subjects who did not have traditional risk factors were more likely to participate in [their] study as it was performed in a hospital and was not population-based”. Unfortunately, the scientific community mostly neglected this information, thus limiting the transferability of the findings to the general population and the interpretation of the correlation between HR-SB and OPSCC in their study [ 1 ]; instead, they interpreted the data from their study as evidence for a causative involvement of HR-SB in the etiology of OPSCC in general.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that we could not detect any HPV integration from 40 HPV16 positive OPSCC by using restriction site oligonucleotide PCR (RSO-PCR) [ 58 ], while the same method was able to identify HPV-human junctions in many cervical cancers [ 39 , 59 , 60 ]. All of these studies together suggest that HPV integrations do occur in OPSCC but that the frequency of integrations may occur less than it does in cervical cancer.…”
Section: Hpv and Opsccmentioning
confidence: 99%